Enhancing students’ L2 writing skills online: a case study of an introductory English literature course for ESL students - Shi Huiwen; Chan Ka-ling Zoe; Wu Wenli; Cheung Lok-ming Eric (Journal of China Computer-Assisted Language Learning)
This research paper is based on a case study of an introductory English literature course that is being offered at a community college in Hong Kong, China. The 2020–2021 cohort was unique as it had the entire course online using Zoom without any face-to-face or hybrid teaching, which was considered the “new normal” of higher education under the pandemic. This study employs narrative inquiry (Barkhuizen, G. (2014). Revisiting narrative frames: An instrument for investigating language teaching and learning. System, 47, 12–27; Clandinin, D. J. (2016). Engaging in narrative inquiry. Routledge), semi-structured interviews, and analysis of student essays to demonstrate that online essay consultations and collaborative writing are useful for enhancing the essay writing skills of second language learners. The paper specifically reports and highlights how individual Zoom essay consultations, together with collaborative writing on Padlet, scaffold and enhance students’ essay writing and critical thinking skills. Essentially, the paper argues that online technologies expand the dimension of literature education and empower it as a form of content-based ESL instruction for long-term use.